Homocysteine thiolactone and H2O2 induce amino acid modifications and alter the fibrillation propensity of the Aβ25–35 peptide. Issue 7 (2nd February 2023) - Bag, Sudipta; Konar, Mouli; Roy, Pritam; DasGupta, Sunando; Dasgupta, Swagata
Abstract : Of the proteinaceous β‐sheet‐rich amyloid fibrillar structures, the Aβ25–35 peptide, a component of the full‐length Aβ involved in Alzheimer's disease, has similar toxicity to the parent peptide. In this study, the effects of homocysteine thiolactone (HCTL) and hydrogen peroxide (H2 O2 ) on the conformation and fibrillation propensity of the Aβ25–35 peptide were investigated. Both HCTL and H2 O2 induced amino acid modifications along with alteration in aggregation propensity. Methionine (Met)‐35 was oxidized by H2 O2 and aggregation was attenuated following the increased hydrophilicity of the peptide due to sulfoxide/sulfone formation. The HCTL‐modified lysine (Lys‐28) residue destabilizes the structure of the peptide, which leads to fibrillation. Our studies provide important information regarding the relationship between amino acid modifications and the amyloid fibrillation process. Abstract : Under physiological conditions in vitro, homocysteine thiolactone‐modified peptides undergo self‐assembly leading to an increment in fibrillation of the Aβ25–35 peptide. Treatment of the peptide with H2 O2 results in Met‐oxidation to polar sulfoxide/sulfone moieties that favour peptide–solvent (water) interactions, resulting in attenuated interactions among the peptide units leading to a lower extent of fibrillation.